Fourier-transform spectroscopy of the H217O molecule between 5200 and 6200 cm−1. (May 2020) - Sinitsa, L.N.; Serdyukov, V.I.; Polovtseva, E.R.; Bykov, A.D.; Scherbakov, A.P.
Highlights: The spectrum of H2 17 O studied between 5200 and 6200 cm −1 for the first time. 173 new transitions to 7 vibrational states determined for the first time. Comparison of experimental H2 17 O absorption versus simulation based on the variational calculation list. Abstract: The absorption spectrum of 17 O-enriched water vapor between 5200 and 6200 cm −1 at room temperature has been recorded using an IFS-125 M Fourier spectrometer. Measurements have been performed at a spectral resolution of 0.02 cm −1 using a halogen lamp and a White cell with an optical path of 24 m. The spectral line parameters have been computed by least squares fitting the Voigt profile to the measured transmittance. The vibrational-rotational assignments have been made based on the theoretical calculations by Polyansky et al. As a result, we have compiled a detailed line list containing over 1000 lines of 10 vibrational-rotational bands and identified 173 new transitions associated with the second triad and the first hexad of interacting vibrational states. Line positions and intensities determined in this work have been compared with the data recommended by the IUPAC group and the experimental data of other authors.